TB specific intracellular cytokines production in Synovial liquid for diagnosis of tuberculous arthritis - Vita, Serena; Mascia, Claudia; Kertusha, Blerta; Marocco, Raffaella; Sauzullo, Ilaria; Mengoni, Fabio; Pozzetto, Irene; Scalzi, Alessandro; Nijhawan, Parni; Savinelli, Stefano; Fondaco, Laura; Carraro, Anna; et al. (The Journal of Infection in Developing Countries, 2023)
Introduction: Skeletal tuberculosis (TB) accounts for about 10 to 35% of extrapulmonary cases and the knee is the most frequent site after the spine and hip. The diagnosis is difficult and largely clinical. Case presentation: This is a case of a young Pakistani man with a history of joint pain for about 4 years, who was diagnosed with chronic arthritis of the right knee. Microscopy of synovial fluid and conventional diagnostic tests to identify Mycobacterium tuberculosis were negative, while a non-classical method based on intracellular cytokine flow cytometry response of CD4 T-cells in synovial fluid helped us to address the diagnosis, which was subsequently confirmed by Polymerase Chain Reaction (PCR). Conclusions: Thanks to an innovative immunological approach, supported by PCR for detection of M. tuberculosis DNA, we were able to diagnose tuberculous arthritis of the knee, which allowed prompt initiation of treatment to reduce morbidity and mortality.